Community Based Correction Method as Implementation of Assimilation Rights for Child Prisoners at the Gorontalo Special Children's Rehabilitation Institution - Abdullah, Wahyu Muhaimin; Kasim, Ramdhan; Nurmala, Leni Dwi (PT. Riset Press International, 2025)
Problems related to children in conflict with the law impact the quality of children as the next generation and national assets. With the high number of children in conflict with the law, proper handling is also needed so that the judicial process for children does not violate the rights inherent in the child, which will negatively impact the child's growth and development process in the future. This study aims to determine how Community-Based Correction is an effort to implement the assimilation rights of child prisoners in Special Child Development Institutions. The research method used in this writing is empirical Juridical research. Legal research on implementing or implementing normative legal provisions in action in every specific legal event that occurs in society. The results of the discussion of this study show that the Special Child Development Institution has a very important role, namely in carrying out guidance for children in conflict with the law. This includes skills training, religious guidance, and intellectual, physical, and spiritual health. One of the guidance programs for prisoners is Community Based Corrections; prisoners are allowed to return to the community and remain under supervision by the Correctional Center. As in the example of external Assimilation, foster children are allowed to participate in skills training and other activities outside the LPKA. So that foster children can mingle with the community and do social work before their detention period ends.